Exclusive transmission of the embryonic stem cell‐derived genome through the mouse germline. Issue 6 (18th May 2016) - Koentgen, Frank; Lin, Jiangwei; Katidou, Markella; Chang, Isabelle; Khan, Mona; Watts, Jacqui; Mombaerts, Peter
Summary: Gene targeting in embryonic stem (ES) cells remains best practice for introducing complex mutations into the mouse germline. One aspect in this multistep process that has not been streamlined with regard to the logistics and ethics of mouse breeding is the efficiency of germline transmission: the transmission of the ES cell‐derived genome through the germline of chimeras to their offspring. A method whereby male chimeras transmit exclusively the genome of the injected ES cells to their offspring has been developed. The new technology, referred to as goGermline, entails injecting ES cells into blastocysts produced by superovulated homozygous Tsc22d3 floxed females mated with homozygous ROSA26‐Cre males. This cross produces males that are sterile due to a complete cell‐autonomous defect in spermatogenesis. The resulting male chimeras can be sterile but when fertile, they transmit the ES cell‐derived genome to 100% of their offspring. The method was validated extensively and in two laboratories for gene‐targeted ES clones that were derived from the commonly used parental ES cell lines Bruce4, E14, and JM8A3. The complete elimination of the collateral birth of undesired, non‐ES cell‐derived offspring in goGermline technology fulfills the reduction imperative of the 3R principle of humane experimental technique with animals. genesis 54:326–333, 2016. © 2016 The Authors. Genesis Published by Wiley Periodicals, Inc.